1985
DOI: 10.1063/1.335280
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric conversion cycle of vinylidene fluoride-trifluoroethylene copolymer

Abstract: Copolymers of vinylidene fluoride-trifluoroethylene P(VDF-TrFE) exhibit large piezoelectric ~Qd pyroelectric effects. In addition to the most common application of the pyroelectric effect (radiant detection) it is possible to'convert heat directly into electrical energy by pyroelectric conversion. This study reports the first pyroelectric conversion cycle to be measured. for the ------,copolymer-F(VDF-1=r:FE) .. It-isfound-that-standard-isotheimal-D-E-hysteresis-loopmeasurements--------are not necessarily accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 11 publications
1
98
0
Order By: Relevance
“…Later, Olsen et al [3] assembled the only multistage device built to date using different grades of lead zirconate stannate titanate (PZST), in which Ti 4+ was substituted by Sn 4+ , for a maximum output of 33 W/L of pyroelectric materials at 0.26 Hz and featuring a maximum thermodynamic efficiency of 1.05% at 0.14 Hz or 12% of the Carnot efficiency. Moreover, due to the cost of PZT ($10,000/Watt), Olsen et al [6] proposed to use inexpensive single stage 73/27 P(VDF-TrFE) films of 30-70 µm thick sandwiched between electrodes and rolled in a spiral stack placed into a cylindrical chamber containing silicon oil. The energy density between 20 and 90 • C achieved 30 mJ/cm 3 -cycle.…”
Section: Direct Pyroelectric Energy Convertermentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Olsen et al [3] assembled the only multistage device built to date using different grades of lead zirconate stannate titanate (PZST), in which Ti 4+ was substituted by Sn 4+ , for a maximum output of 33 W/L of pyroelectric materials at 0.26 Hz and featuring a maximum thermodynamic efficiency of 1.05% at 0.14 Hz or 12% of the Carnot efficiency. Moreover, due to the cost of PZT ($10,000/Watt), Olsen et al [6] proposed to use inexpensive single stage 73/27 P(VDF-TrFE) films of 30-70 µm thick sandwiched between electrodes and rolled in a spiral stack placed into a cylindrical chamber containing silicon oil. The energy density between 20 and 90 • C achieved 30 mJ/cm 3 -cycle.…”
Section: Direct Pyroelectric Energy Convertermentioning
confidence: 99%
“…In fact, in 2002 more than 50% of the net primary energy resource consumption in the U.S. was lost mainly in the form of waste heat [1]. Pyroelectric energy converter offers a novel direct energy conversion technology by directly transforming waste heat into electricity [2][3][4][5][6][7][8][9][10][11][12]. It makes use of the pyroelectric effect to create a flow of charge to or from the surface of a material as a result of successive heating or cooling cycles [13].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it is found that fluorinated polymers and especially terpolymers have enormous potential for energy harvesting from heat due to its large pyroelectric activity. In 1985, Olsen et al reported the first pyroelectric conversion cycle for the copolymer P(VDF-TrFE), the output electrical energy density was 30 mJ/cm 3 , which is 15 times larger than any other polymer previously measured 2 . In 2010, Nguyen et al developed the pyroelectric energy converter using copolymer 60/40 P(VDFTrFE) and based on Ericsson cycle 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of polymers opens up novel possibilities for multi-source energy harvesting technique. In view of thermal energy harvesting, the use of copolymer P(VDF-TrFE) to harvest waste heat by pyroelectricity has been explored both experimentally and theoretically [2][3][4] . In this part, we are interested in energy harvesting from nonlinear capacitance variation by temperature on terpolymer P(VDF-TrFE-CFE) 13 .…”
Section: Terpolymer P(vdf-trfe-cfe)mentioning
confidence: 99%
“…A large advancement was obtained in the field of pyroelectric conversion by Olsen's Group [38,39]. They proposed the first pyroelectric conversion cycle named 'Olsen cycle' or 'Ericsson cycle' (electric analogous of the Ericsson heat engine cycle).…”
Section: Thermal Energy Harvestingmentioning
confidence: 99%